2017
DOI: 10.1002/oby.21864
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial reveals that physical activity and energy expenditure are associated with weight and body composition after RYGB

Abstract: ObjectiveWe investigated the associations of both physical activity time (PA) and energy expenditure (EE) with weight and fat mass (FM) loss in patients following Roux-en-Y gastric bypass (RYGB) surgery.MethodsNinety-six non-diabetic patients were included in this analysis. Post RYGB patients were randomized in one of two treatments: A 6-month exercise training program (RYBG+EX) or lifestyle educational classes (RYGB). Body composition was assessed by dual-energy X-ray absorptiometry and computed tomography. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 40 publications
0
63
0
17
Order By: Relevance
“…On the other hand, in evaluating the relationship between the body composition measures and knee OA, we used potential confounders for adjustment such as physical activity, which is known to affect body composition by losing fat mass and maintaining muscle mass which is a surrogate of lean mass. [35] In conclusion this study shows that body weight is significantly and positively associated with knee OA and, among the components that constitute body weight, fat mass is closely and significantly associated with knee OA in postmenopausal women when assessed together with lean mass. This result suggests that the relationship between obesity and knee OA is mainly based on the fat mass, and supports the importance of systemic metabolic effects of adiposity in this relationship.…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, in evaluating the relationship between the body composition measures and knee OA, we used potential confounders for adjustment such as physical activity, which is known to affect body composition by losing fat mass and maintaining muscle mass which is a surrogate of lean mass. [35] In conclusion this study shows that body weight is significantly and positively associated with knee OA and, among the components that constitute body weight, fat mass is closely and significantly associated with knee OA in postmenopausal women when assessed together with lean mass. This result suggests that the relationship between obesity and knee OA is mainly based on the fat mass, and supports the importance of systemic metabolic effects of adiposity in this relationship.…”
Section: Discussionmentioning
confidence: 53%
“…All but two subjects wore the armband for seven consecutive days at baseline and during the last week of intervention. Analyses were performed on all days where the monitors were worn >90% of the day as presented elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, a limitation of this study is that it does not provide body composition measurements, which preclude any direct conclusion on muscular mass changes. However, numerous studies have previously indicated that lean body mass loss occurs with post-surgery fat mass loss [10,12,13,16,18,36]. Lower muscle mass and oxidative capacity would indeed lead to a deconditioned profile with a low absolute VO 2 max and VT1.…”
Section: Muscular and Metabolic Limitationmentioning
confidence: 99%